Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
- See below
Step-by-step explanation:
Given equation:
- 3x² + 5x + 2 = 0
Factorize it in steps:
- 3x² + 5x + 2 = 0
- 3x² + 3x + 2x + 2 = 0
- 3x(x + 1) + 2(x + 1) = 0
- (x + 1)(3x + 2) = 0
The roots are:
- x + 1 = 0 ⇒ x = - 1
- 3x + 2 = 0 ⇒ 3x = - 2 ⇒ x = - 2/3
[tex]\\ \tt\hookrightarrow 3x^2+5x+2=0[/tex]
- Split the middle term
[tex]\\ \tt\hookrightarrow 3x^2+3x+2x+2=0[/tex]
- Take commons
[tex]\\ \tt\hookrightarrow 3x(x+1)+2(x+1)=0[/tex]
[tex]\\ \tt\hookrightarrow (3x+2)(x+1)=0[/tex]
[tex]\\ \tt\hookrightarrow x=\dfrac{-2}{3}\:or\:x=-1[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.